A preliminary research study on the cytotoxicity of expired and non-expired composite resins : in vitro study = Estudio preliminar in vitro de la citotoxicidad de resinas compuestas caducadas y no caducadas - Kazak, Magrur; Donmez, Nazmiye; Bahadori, Fatemeh; Betul Yenigun, Vildan; Kocyigit, Abdurrahim (2020)
Objective: Studies have focused on use of non-expired composites. Unfortunately some clinicians still use expired composite resins without considering their effects. The objective of this in vitro preliminary research was to investigate cytotoxicity of expired(6-months) and non-expired composite resins. Materials and methods: Expired (E) and non-expired (NE) samples of one bulk-fill (Tetric N-Ceram Bulk-fill [TNB], Ivoclar Vivadent), two nano-hybrid (Tetric N-Ceram [TN], Ivoclar Vivadent; Clearfil Majesty ES-2 [CM], Kuraray) composite resins were tested on L929 fibroblast cells. Medium covering cells was removed then plastic rings (2-mm height) were filled with non-polymerized composite resins, placed in direct contact with cells and polymerized with LED light curing unit (LCU). Three samples were prepared for each group. After polymerization, removed medium was added to the cells. Cells that were left without medium (WOM) and cells that were exposed to LCU were used as positive control groups. Cells without any treatment were used as negative control group (C). Cells were incubated with tested materials for 7-days to evaluate cytotoxicity. Cell viability was calculated by sulforhodamine B test as a percentage (%). One-way ANOVA and post-hoc Tukey tests were used for statistical analyses (p<0.05). Results: Comparison between E and NE groups of same composite resins did not result in statistically significant differences (p>0.05), except between TN NE and TN E (p<0.05). TN E group was significantly more cytotoxic than TN NE group. When NE composite resin groups were compared to each other, statistically significant difference was only obtained between TNB NE and TN NE (p<0.05). Among all tested groups, TN NE group showed the least cytotoxic profile. No statistically significant differences were determined when E composite resin groups were compared to each other (p>0.05). All experimental groups compared with C group showed statistically significant...
Objetivo: Los estudios se han concentrado en el uso de resinas compuestas no vencidos. Desafortunadamente, algunos clínicos aún usan resinas caducadas sin considerar sus efectos. El objetivo de este estudio preliminar in vitro fue investigar la citotoxicidad de resinas compuestas caducadas (6 meses) y no caducadas. Materiales y métodos: muestras caducadas (E) y no caducadas (NE) de una resina bulk-fill (Tetric N-Ceram Bulk-fill [TNB], Ivoclar Vivadent) y dos resinas nanohíbridas (Tetric N-Ceram [TN]) Ivoclar Vivadent) (Clearfil Majesty ES-2 [CM], Kuraray), se probaron en células de fibroblastos L929. Se retiraron las células que cubrían el medio, luego se llenaron anillos de plástico (2 mm de altura) con resinas no polimerizadas, se colocaron en contacto directo con las células y se polimerizaron con una unidad de fotocurado LED (LCU). Se prepararon tres muestras para cada grupo. Después de la polimerización, se añadió el medio eliminado a las células. Las células que quedaron sin medio (WOM) y las células que se expusieron a LCU se usaron como grupos de control positivo. Las células sin ningún tratamiento se utilizaron como grupo de control negativo (C). Las células se incubaron con las resinas durante 7 días para evaluar la citotoxicidad. La viabilidad celular se calculó mediante la prueba de sulforodamina B como un porcentaje (%). ANOVA unidireccional y pruebas post-hoc de Tukey se utilizaron para los análisis estadísticos (p <0.05). Resultados: La comparación entre los grupos E y NE de las mismas resinas compuestas no mostraron diferencias estadísticamente significativas (p> 0.05), excepto entre TN NE y TN E (p <0.05). El grupo TN E fue significativamente más citotóxico que el grupo TN NE. Cuando los grupos de resinas compuestas de NE se compararon entre sí, solo se obtuvo una diferencia estadísticamente significativa entre TNB NE y TN NE (p <0.05). Entre todos los grupos probados, el grupo TN NE mostró el perfil menos...
En revista Odóvtos, vol. 22, no. 3 (septiembre-diciembre 2020)
Descripción basada en el contenido visto el 11 de octubre, 2024
También disponible en formato HTML y EPUB